2013
DOI: 10.1007/978-1-4614-6093-0_12
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Serum Taurine, Serum Adipokines, and Body Composition During 8-Week Human Body Weight Control Program

Abstract: Human adipose tissue is not only a storage organ but also an active endocrine organ to release adipokines. This study was conducted to investigate the relationship among serum taurine and adipokine levels, and body composition during 8-week human body weight control program in obese female college students. The program consisted of diet therapy, exercise, and behavior modification. After the program, body weight, body fat mass, percent body fat, and body mass index (BMI) were significantly decreased. Serum tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Generally, serum leptin level is positively associated with fat mass. (32) In our study, fat mass was highest in the isocaloric administration HFS diet group and lowest in the CR diet group. Therefore, the leptin level reflected fat mass.…”
Section: Discussionsupporting
confidence: 46%
“…Generally, serum leptin level is positively associated with fat mass. (32) In our study, fat mass was highest in the isocaloric administration HFS diet group and lowest in the CR diet group. Therefore, the leptin level reflected fat mass.…”
Section: Discussionsupporting
confidence: 46%
“…Different studies show that protein carbonylation, lipid peroxidation, oxLDL and 8-isoprostane, as well as inflammatory markers (such as C-reactive protein, IL-8 and genes involved in the TNF-α/NF-kB signal cascade), decline with weight reduction [122126]. Metabolic functions ameliorate with reduction in oxidative stress, as evidenced by increased adiponectin levels and better liver function [127]. At a molecular level, lowering energy supply activates proteins of the sirtuin (SIRT) and Forkhead box, sub-group O (FoxO) families [128]: sirtuin are NAD + -dependent deacetylases that transcriptionally improve metabolic efficiency, strengthen antioxidant defenses and dampen inflammatory activities [129], while FoxO proteins modulate transcription of genes involved in energy homeostasis, cell survival and inflammatory responses, including NF-κB [130].…”
Section: Potential Strategies To Reduce Oxidative Stress In Obesitymentioning
confidence: 99%
“…While many studies have shown that serum leptin concentrations decrease following weight loss [14, 22-36], the relationship between serum adiponectin concentrations and weight loss is less clear, although some studies indicate that adiponectin concentrations increase following weight loss [24-26, 29, 36-42]. Similarly, the effect of exercise on serum adipokines is also unclear.…”
Section: Discussionmentioning
confidence: 99%